Block Length‐Dependent Protein Fouling on Poly(2‐oxazoline)‐Based Polymersomes: Influence on Macrophage Association and Circulation Behavior. Issue 27 (7th June 2022) - Najer, Adrian; Belessiotis‐Richards, Alexis; Kim, Hyemin; Saunders, Catherine; Fenaroli, Federico; Adrianus, Christopher; Che, Junyi; Tonkin, Renée L.; Høgset, Håkon; Lörcher, Samuel; Penna, Matthew; Higgins, Stuart G.; et al.
Abstract: Polymersomes are vesicular structures self‐assembled from amphiphilic block copolymers and are considered an alternative to liposomes for applications in drug delivery, immunotherapy, biosensing, and as nanoreactors and artificial organelles. However, the limited availability of systematic stability, protein fouling (protein corona formation), and blood circulation studies hampers their clinical translation. Poly(2‐oxazoline)s (POx) are valuable antifouling hydrophilic polymers that can replace the current gold‐standard, poly(ethylene glycol) (PEG), yet investigations of POx functionality on nanoparticles are relatively sparse. Herein, a systematic study is reported of the structural, dynamic and antifouling properties of polymersomes made of poly(2‐methyl‐2‐oxazoline)‐ block ‐poly(dimethylsiloxane)‐ block ‐poly(2‐methyl‐2‐oxazoline) (PMOXA‐ b ‐PDMS‐ b ‐PMOXA). The study relates in vitro antifouling performance of the polymersomes to atomistic molecular dynamics simulations of polymersome membrane hydration behavior. These observations support the experimentally demonstrated benefit of maximizing the length of PMOXA (degree of polymerization ( DP ) > 6) while keeping PDMS at a minimal length that still provides sufficient membrane stability ( DP > 19). In vitro macrophage association and in vivo blood circulation evaluation of polymersomes in zebrafish embryos corroborate these findings. They further suggest that single copolymer presentation on polymersomes is outperformed by blends of varied copolymer lengths. This study helps to rationalize design rules for stable and low‐fouling polymersomes for future medical applications. Abstract : Stability, protein fouling, in vitro and in vivo behavior of poly(2‐methyl‐2‐oxazoline)‐ block ‐poly(dimethylsiloxane)‐ block ‐poly(2‐methyl‐2‐oxazoline) (PMOXA‐ b ‐PDMS‐ b ‐PMOXA) polymersomes are studied as a function of relative block lengths and copolymer blends. Atomistic simulations reveal the importance of interfacial water and confirm the experimental conclusions of maximizing PMOXA and minimizing PDMS content for improved performance. This systematic study is key for moving polymersomes closer to clinical translation.